Delicates - Thummler, Brenna (Oni Press, 2021)
Marjorie Glatt's life changed forever when she discovered a group of ghosts living in her family's laundromat. Now, she has a friend in Wendell, one of the ghosts, and feels less alone in the world. But when Marjorie gets accepted by the popular kids at school, she realizes she has to keep Wendell a secret and doing this causes Wendell to feel even more invisible. Soon, Marjorie's life intersects with Eliza, a fellow classmate who is obsessed with photographing ghosts and is being bullied by Marjorie's new friends.